Freelance Language Teachers' Professional Development On ... And With ... And Through Twitter - Emke, Martina
In recent years more and more freelance teachers have been employed in higher education and in further education, and they often struggle with barriers to professional development. Freelance language teachers are understood to work within various (self-) employment situations, often across educational sectors. For these teachers, access to professional development can be particularly challenging. Previous research has suggested that teachers’ use of the social media platform Twitter could lead to effective professional development (Carpenter & Krutka, 2014) and foster the formation of community among language educators (Wesely, 2013; Lord & Lomicka, 2014). Twitter is an Internet platform which enables registered users to communicate via text messages (tweets). While phenomenological research approaches have provided valuable insight into human experiences and perceptions of Twitter for professional learning, they tend to overlook the relational, human and non-human complexities involved (with)in the enactment of human practices. Drawing on the Deleuzo-Guattarian concepts of rhizome, assemblage and becoming (Deleuze & Guattari, 1987), this doctoral research seeks to provide answers to questions concerning how language teachers’ professional development on…and with…and through Twitter works and what it produces. Research data included online narrative frame questionnaires, tweets and online participant interviews. Data enquiry involved the working(s)-together of situational maps (Clarke, 2005) and social network analysis (Newman, 2010). This research suggests professional development and language teaching can be conceived of as entangled practices within human and non-human assemblages, which have the capability to produce unpredictable becomings, rather than as two distinct elements of a binary relationship. Recommendations from this investigation aim to make language educators, language education providers and education policy aware of the relational workings of social media practices, and to provide concrete suggestions for actions that connect with existing practices and programmes to improve freelance language teachers’ professional development.